DESTRUCTION YANUKOVICH REGIME THROUGH PRISM «CRISIS SYNDROME OF MODERNIZATION» - Пояркова, Т. К. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article is devoted to the system analysis of the reasons of Yanukovich regime destruction in the context of «crisis syndrome of modernization» notion. The advantage of this approach is the opportunity to study the indicated events in the frame of the process that is in the phase on dysfunction features collecting, the phase of intensification (with multiple intensive manifestations of crisis of legitimacy, identification, participation, distribution and spreading) and the phase that may appear in the case when overcoming of political system dysfunction doesn’t occur.